Assessing the Impact of Trucking Infrastructure on Freight Efficiency and Safety - Gorzelanczyk, Piotr; Czech, Jakub; Olechnowicz, Jolanta (Communications - Scientific Letters of the University of Zilina, 2023)
The change in people's lifestyles, their desire or compulsion to move constantly and the development of technology, have forced development of communications, which has led, among other things, to an intensive increase in traffic. For this reason, the purpose of the article is to identify the main causes of traffic delays and the factors affecting the sense of safety on the road. It is followed by the analytical part, which presents the effect of a survey conducted on a group of 401 respondents. The respondents' answers show that the most common causes of road accidents and collisions are: failure to adjust the speed to road conditions (89 %), failure to give priority (84 %), which is in line with the 2019 police report. The results show a clear difference between Western Europe and Eastern Europe.
Keywords: road infrastructure; Poland; Europe; road safety; road transport